Strategi Pembelajaran Bahasa Arab Berbasis Neurosains: Arabic Language Learning Strategy Based on Neuroscience - Akhsani Sholihati Yasri; Suyadi Suyadi (Universitas Ahmad Dahlan, 2022)
The rapid development of Arabic language learning, both in curriculum and learning strategies, encourages educational institutions to innovate in Arabic language learning. So far, learning Arabic as monotonous, boring learning and learning activities are more often dominated by teachers. This paper discusses strategies in Arabic language learning that maximize creative skills based on neuroscience. This type of research uses literature review methods, including activities that are carried out systematically to collect, carry out the processing, and carry out data collection using techniques to obtain answers to the problems analyzed. The results of this study are strategies that can be used in Arabic lessons that use a base on the right brain, such as SCAMPER. This includes strategies that give attention to shaping the creativity of students. Students are encouraged to be more creative in carrying out various steps on the SCAMPER strategy. Therefore, it can form creative writing habits so that it has an impact on the development of thinking abilities and skills.